Using Prototypes in Agile Software Development - Ali Hamzah Obaid, (المجلة الدولية للحاسبات والمعلوماتية, 2024)
Prototyping has now become an important and essential part of software development processes. As it is considered one of the ideal ways to receive new jobs through changing requirements during the development process due to its speed and efficiency in delivering models that simulate the final model and its ability to be developed and changed according to the opinions of stakeholders.Agile development and its iterative advantage and adaptability to changing requirements from stakeholders allows business teams to clearly and accurately understand requirements.This paper explores that the use of prototyping in agile software development has an essential role in early and continuous verification of requirements in the development process through the creation of quick, concrete models of proposed features and functionality. This helps in identifying errors, problems or misunderstandings early in the process. Development and this understanding helps save time and material costs allocated to the development process. Using prototypes and integrating them into agile development helps work teams and stakeholders adapt flexibly, obtain a clear vision of requirements, and identify weak points in the development process by holding meetings and Periodic meetings to obtain a highly efficient product that meets their desires and the desires of end users.